Are we correctly managing marine resources in Costa Rica? - Jiménez Ramón, Jorge A. (2023)
Abstract The exploitation of coastal-marine resources has occurred in our coasts since about 12 000 years ago. This activity has been intense and careless regarding to the well-being of the resource being exploited. Consequently, many of the resources have collapsed throughout the centuries. Pearls, tortoiseshell, mother-of-pearl, turtles, mangrove-cockle, and many other species have stopped being commercially viable. Presently, fisheries, formerly believed inexhaustible, also show unequivocal signs of overexploitation.  Far from improving, our relationship with marine resources has exacerbated. The exploitation increment, combined with contamination and ocean warming, have deteriorated these resources. Essential biomass and population status analyses continue to be neglected, even after the founding of INCOPESCA in 1994. Total ship landings, between 2000-2015 have decreased 45 % impacting particularly the artisanal fleet.  The number of fishing vessels have gone from 5 000 in 2010 to less than 2 000 four years later and the number of jobs in the sector has decreased by 50 %. It is urgent to have an institution able to generate information that allow us to determine the level and manner of this exploitation. Such management needs to be independent of economic and political interests and should be coupled with an efficient and effective administration, together with strict control and surveillance of this activity.